Building and Strengthening Social Awareness in the Formation of Clean and Healthy Living Behaviors in Children of the Independent People's School Community of Central Kalimantan - Muhammad Hayyan Akbar; Zuwariyah Kartini; Januarti Litania Hutajulu; Putri Amelia; Wiwin Pahlentesa; Saputra Adiwijaya; Ida Bagus Suryanath (PT Polstac Repositori Riset, 2026)
Background: This community service program aims to increase the understanding and practice of Clean and Healthy Living Behavior (PHBS) in children at Sekolah Rakyat Merdeka Kalteng (SRMK) through education and simulations on how to wash hands correctly. Contribution: This activity was carried out using counseling methods, demonstrations, educational games, and hands-on practice, equipped with pre-tests and post-tests to evaluate changes in knowledge. Method. Data were collected through observations, interviews with parents, and literature studies. The results of the pre-test showed that 95% of participants did not understand the correct handwashing steps, while the post-test results showed an increase in understanding to 87.5%. Results: These findings confirm the effectiveness of interactive methods in teaching healthy behaviors from an early age. Analysis with the perspective of Bourdieu's habitus shows that children's hygiene habits are greatly influenced by the social, cultural, and economic capital owned by the family, so that the role of parents is a key factor in the sustainability of healthy behavior. The program highlights that comprehensive educational interventions, involving children as well as their family environments, can be a significant strategy to encourage sustainable health behavior change in vulnerable communities.